Adapting IAPT services to support frontline NHS staff during the Covid-19 pandemic: the Homerton Covid Psychological Support (HCPS) pathway. (2020) - Cole, C.L.; Waterman, S.; Stott, J.; Saunders, R.; Buckman, J.E.J.; Pilling, S.; Wheatley, J.
Abstract: The Coronavirus (Covid-19) pandemic is exerting unprecedented pressure on NHS Health and Social Care provisions, with frontline staff, such as those of critical care units, encountering vast practical and emotional challenges on a daily basis. Although staff are being supported through organisational provisions, facilitated by those in leadership roles, the emergence of mental health difficulties or the exacerbation of existing ones amongst these members of staff is a cause for concern. Acknowledging this, academics and healthcare professionals alike are calling for psychological support for frontline staff, which not only addresses distress during the initial phases of the outbreak but also over the months, if not years, that follow. Fortunately, mental health services and psychology professional bodies across the United Kingdom have issued guidance to meet these needs. An attempt has been made to translate these sets of guidance into clinical provisions via the recently established Homerton Covid Psychological Support (HCPS) pathway delivered by Talk Changes (Hackney & City IAPT). This article describes the phased, stepped-care and evidence-based approach that has been adopted by the service to support local frontline NHS staff. We wish to share our service design and pathway of care with other Improving Access to Psychological Therapies (IAPT) services who may also seek to support hospital frontline staff within their associated NHS Trusts and in doing so, lay the foundations of a coordinated response. Key learning aims: (1) To understand the ways staff can be psychologically and emotionally impacted by working on the frontline of disease outbreaks. (2) To understand the ways in which IAPT services have previously supported populations exposed to crises. (3) To learn ways of delivering psychological support and interventions during a pandemic context based on existing guidance and research.